Who Gets to Play? Disability, Open Literacy, Gaming - Ellis Katie; Kao Kai-Ti (Cultural Science)
Video games are an expanding area of popular culture spanning traditional age, gender and socioeconomic divides and appealing to a diverse market. People with disability represent a significant but under researched gaming demographic (Beeston et al., 2018). While this group represent a large portion of the gaming population, inaccessible interfaces and consoles may prevent people with disability from playing games. Despite this, research dating back to 2008 suggests 92% of gamers with disability continue to play games despite these obstacles. This paper aims to put the topic of gamers with disabilities on the agenda for Open Literacies.